Interfacial interactions between Skeletonema costatum extracellular organic matter and metal oxides: Implications for ceramic membrane filtration - Zaouri, N.; Gutierrez, L.; Dramas, L.; Garces, D.; Croue, Jean-Philippe (IWA Publishing, 2017)
In the current study, the interfacial interactions between the high molecular weight (HMW) compounds of Skeletonema costatum (SKC) extracellular organic matter (EOM) and ZrO2 or Al2O3, were investigated by atomic force microscopy (AFM). HMW SKC-EOM was rigorously characterized and described as a hydrophilic organic compound mainly comprised of polysaccharide-like structures. Lipids and proteins were also observed, although in lower abundance. HMW SKC-EOM displayed attractive forces during approaching (i.e., leading to jump-to-contact events) and adhesion forces during retracting regime to both metal oxides at all solution conditions tested, where electrostatics and hydrogen bonding were suggested as dominant interacting mechanisms. However, the magnitude of these forces was significantly higher on ZrO2 surfaces, irrespective of cation type (Na+ or Ca2+) or concentration. Interestingly, while HMW SKC-EOM interacting forces to Al2O3 were practically insensitive to solution chemistry, the interactions between ZrO2 and HMW SKC-EOM increased with increasing cation concentration in solution. The structure, and lower charge, hydrophilicity, and density of hydroxyl groups on ZrO2 surface would play a key role on favoring zirconia associations with HMW SKC-EOM. The current results contribute to advance our fundamental understanding of Algogenic Organic Matter (AOM) interfacial interactions with metal oxides (i.e., AOM membrane fouling), and would highly assist in the proper selection of membrane material during episodic algal blooms.